Evaluation the efficiency of some insecticides and Bio-agent Trichoderma harizanium against Colaphellus apicalis Mentr (Coleoptera Chrysomelidae ) in the field - Baqir, Hussein Ali (Journal of Kerbala for Agricultural Sciences, 2016)
Field experiment were carried out to investigate the effectiveness of some insecticides Actara (Thiamethoxam), Avaunt(Indoxacarb) and Karate(Lambda cyhalothrin) and Bio-Agent Trichoderma harizanium against larvae and adult stages of Radish beetle Colaphellus apicalis Mentr (Coleoptera Chrysomelidae ).The results showed that Avaunt and Actara were the best effective and gave mortality of larvae 90.42 and 88.51%, respectively .while Karate gave 80..85% mortality of larvae. The results showed almost similar effect of Avaunt and Actara against adult and gave mortality of adult 83.84and 79.4%, respectively whereas Karate gave 77.33%.The study also showed that spore suspension of Trichoderma harzianum caused a high mortality against larvae and adult stages of Colaphellus apicalis Mentr reached 61.22and 53.08%, respectively. When used at concentration 1×1012 after seven day from spraying. The results reveal that the mortality increased when exposure period was increased.